What can't colostrum do? Exploring the effects of supplementing colostrum after the first day of life: A narrative review* - David L. Renaud; Michael A. Steele (JDS Communications)
The objective of this narrative review is to explore the nontraditional uses of colostrum in dairy calves beyond the first and second feeding after birth. Colostrum is well established as a crucial component of early life management in dairy calves, providing essential antibodies for passive immunity. However, recent studies suggest that extending colostrum supplementation beyond the initial feedings, as well as incorporating transition milk, can yield benefits for calf health and development. Research indicates that such supplementation may lead to enhancements in gut development, improved health scores, and reduced incidence of diseases such as diarrhea and respiratory disease. Furthermore, recent findings have highlighted colostrum's potential to aid in the recovery from diarrhea and support calves during the weaning phase. Despite these findings, the exact mechanisms behind these benefits are still unclear, necessitating further research. Additionally, studies with larger sample sizes and varied housing conditions are needed to fully elucidate colostrum's benefits beyond the first day of life.